(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine whether the executive characters and leverage can affect tax avoidance in Indonesia Mining and Coal Listed Companies. The factors tested in this study were the executive character and leverage with the proxies corporate risk and debt to equity, respectively, as independent variables. Meanwhile, tax avoidance is proxied by cash effective tax rate as the dependent variable.The research data are taken from 112 financial statements of 28 Indonesian Mining and Coal Companies that listed on the Indonesia Stock Exchange in the period 2016 - 2019. The data are analyzed by using panel data regression analysis.The research results show that that executive characteristic has significant positive effect on tax avoidance. In constrast, the leverage has not effect on tax avoidance.